Prothrombotic Genotypes Are not Associated with Pre-eclampsia and Gestational Hypertension: Results from a Large Population-based Study and Systematic Review - Morrison, E. R.; Miedzybrodzka, Z. H.; Campbell, D. M.; Haites, N. E.; Wilson, B. J.; Watson, M. S.; Greaves, M.; Vickers, M. A. (Thrombosis and Haemostasis, 2002)
DNA samples collected as part of a large population-based casecontrol study were genotyped to examine the associations of five prothrombotic gene polymorphisms with pre-eclampsia (PE) and gestational hypertension (GH). The polymorphisms studied were: G1691A in Factor V (Factor V Leiden; FVL), prothrombin G20210A, methylenetetrahydrofolate reductase (MTHFR) C677T, plasminogen activator inhibitor-1 4G/5G and the platelet collagen receptor α2β1 C807T. A group of 404 women who developed PE were retrospectively compared with 303 women with GH and 164 control women. The frequency of genotypes did not differ significantly between cases of PE or GH and controls for any of the five polymorphisms studied. We conclude that these prothrombotic genotypes are not associated with the development of PE or GH in our population. The systematic review supports our conclusion, for all but cases of severe disease, which appear to be associated with FVL and, to a lesser extent, MTHFR C677T. There is little value in antenatal screening for prothrombotic polymorphisms to predict the development of pre-eclampsia or gestational hypertension.
Keywords: Pre-eclampsia; gestational hypertension; prothrombotic polymorphisms; Factor V Leiden; MTHFR